2022
DOI: 10.1093/eurheartj/ehac576
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for cardiac implantable electronic device infections: a nationwide Danish study

Abstract: Aims Cardiac implantable electronic device (CIED) infection is a severe complication to modern management of cardiac arrhythmias. The CIED type and the type of surgery are recognized as risk factors for CIED infections, but knowledge of patient-related risk factors is scarce. This study aimed to identify lifelong patient-related risk factors for CIED infections. Methods and results Consecutive Danish patients undergoing a CIE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 76 publications
0
21
0
Order By: Relevance
“…That may indicate multiple entry points, a temporary deficit of immunocompetency, or the presence of more severe comorbidities, resulting in a greater failure rate of both medical and non-pharmacological therapy. The incidence of patients diagnosed with severe BSI leading to hospitalization was around 22 per 1000 patient-years, hence considerably higher compared with the incidence rate of 2.5 per 1000 device-years after device implantation reported by Olsen et al , 32 who collected data from three nationwide registries: the Danish National Patient Registry, the Danish National Prescription Registry, and the Danish Pacemaker and ICD Register. Considering that patient characteristics at first device implant were similar between our population and the Danish study, it is reasonable to assume that around 1 out of 10 device patients admitted to a hospital with BSI will have a systemic device infection or endocarditis.…”
Section: Discussionmentioning
confidence: 71%
“…That may indicate multiple entry points, a temporary deficit of immunocompetency, or the presence of more severe comorbidities, resulting in a greater failure rate of both medical and non-pharmacological therapy. The incidence of patients diagnosed with severe BSI leading to hospitalization was around 22 per 1000 patient-years, hence considerably higher compared with the incidence rate of 2.5 per 1000 device-years after device implantation reported by Olsen et al , 32 who collected data from three nationwide registries: the Danish National Patient Registry, the Danish National Prescription Registry, and the Danish Pacemaker and ICD Register. Considering that patient characteristics at first device implant were similar between our population and the Danish study, it is reasonable to assume that around 1 out of 10 device patients admitted to a hospital with BSI will have a systemic device infection or endocarditis.…”
Section: Discussionmentioning
confidence: 71%
“…The low incidence of CIED-related infections may be explained by strict adherence to sterile and proper surgical techniques, antibiotic prophylaxis consistently performed in all patients and high operator experience (all cases were performed by expert electrophysiologists working in a tertiary referral center). In a recent study by Olsen et al [ 15 ], the median time to CIED infection was 296 (68–946) CIED-days, with systemic infections occurring significantly later than pocket infections. The former appeared to be associated with risk factors predisposing patients to bacteremia, while the latter was associated with surgery-related factors.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic prophylaxis in patients potentially not represented by the previously mentioned protocol was discussed with the infectious disease specialist and tailored accordingly. An antibiotic-eluting envelope was used only in ICD/CRT patients deemed at high risk of infection according to a PADIT score > 6 [ 13 ] or dialysis [ 14 , 15 ]. The prevention of CIED infection before, during and after the implantation procedure was performed according to current guidelines/consensus documents [ 8 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…[129][130][131] However, electronic pacemakers have been associated with several drawbacks, including electrochemical reactions at the electrode tissue interface, invasive surgery, repeated battery replacement, infection risk, and equipment failure. [132][133][134][135][136] Optogenetic technology, which involves transmitting various opsins to the heart through viral vectors and controlling heart rate through depolarization or repolarization stimulation, presents a promising alternative to electronic pacemakers. 137,138 Research has demonstrated that pacing the heart at multiple sites reduces activation time, thus leading to highly synchronized ventricular activation through the fusion of multiple wave fronts generated simultaneously by all chr2 expression sites.…”
Section: Genetic and Heart Light Systemmentioning
confidence: 99%
“…In the clinical management of chronic arrhythmia and heart failure due to different ventricular pacings, the electronic pacemaker has been the predominant treatment 129–131 . However, electronic pacemakers have been associated with several drawbacks, including electrochemical reactions at the electrode tissue interface, invasive surgery, repeated battery replacement, infection risk, and equipment failure 132–136 . Optogenetic technology, which involves transmitting various opsins to the heart through viral vectors and controlling heart rate through depolarization or repolarization stimulation, presents a promising alternative to electronic pacemakers 137,138 .…”
Section: Applications Of Optogenetics In Various Fieldsmentioning
confidence: 99%